Digital Marketing Training for MSMEs in Surabaya - Lena Ellitan (CV. Ulil Albab Corp, 2023)
Advances in information technology play a very important role in human life. By mastering information technology, humans have sufficient capital to become winners in global competition. Digital marketing (digital marketing) is defined as the use of digital technology to achieve marketing goals as well as efforts to develop or adapt the marketing concept itself, to be able to communicate on a global scope, and change the way companies do business with customers. The development of information technology is growing rapidly. Most Micro, Small and Medium Enterprises (MSMEs) activities utilize information technology to run their business. The increasing number of competitors is a consideration for business actors to innovate in winning the competition. The right marketing communication strategy is used to be able to reach the target market share so as to increase sales. One way to keep even increasing sales is to utilize the right marketing strategy through e-marketing or digital marketing. Marketing is a business process that seeks to align the human, financial and physical resources of an organization with the needs and wants of its customers in the context of a competitive strategy. Therefore it is necessary to do training and mentoring.